Perancangan Stetoskop Elektronik Dan Aplikasi Analisa Suara Jantung Dengan Pengolahan Sinyal Digital - Arya Adhi Nugraha (Jurnal Jaringan Telekomunikasi, 2015)
In this paper and has implemented a stethoscope electronic application sound analysis in heart client-server. A stethoscope electronics will catch a heart and menghantarkannya to computer so that the computer can sound mendigitalisasi heart. The application will process, sound analysis heart store and display a heart condition and sound spectrum of the heart. Extraction habitude anything undertaken to gain special habitude from the heart to perform the process of decomposing paket wavelet and root mean square ( rms ) at the sound of the heart. From the data obtained, in different heart conditions, decomposition of wavelet package give value range min 6 up to a maximum of 23 is much larger and RMS only give minimal range 0.04 to 0.16 in band 0-125Hz of variations of the same types of heart conditions. Sample Data obtained from 5 persons recorded sound his heart and then analyzed with the same two methods. The Data obtained are more closer to the normal heart sound so it can be deduced from the 5 sample data used is the sound of the heart under normal conditions.